Community pharmacists' experiences in mental illness and addictions care: a qualitative study. Issue 1 (December 2016) - Murphy, Andrea; Phelan, Heather; Haslam, Scott; Martin-Misener, Ruth; Kutcher, Stan; Gardner, David
Abstract Background Community pharmacists are accessible health care professionals who encounter people with lived experience of mental illness and addictions in daily practice. Although some existing research supports that community pharmacists' interventions result in improved patient mental health outcomes, gaps in knowledge regarding the pharmacists' experiences with service provision to this population remain. Improving knowledge regarding the pharmacists' experiences with mental illness and addictions service provision can facilitate a better understanding of their perspectives and be used to inform the development and implementation of interventions delivered by community pharmacists for people with lived experience of mental illness and addictions in communities. Methods We conducted a qualitative study using a directed content analysis and the Theoretical Domains Framework as part of our underlying theory of behaviour change and our analytic framework for theme development. The Theoretical Domains Framework facilitates understanding of behaviours of health care professionals and implementation challenges and opportunities for interventions in health care. Thematic analysis co-occurred throughout the process of the directed content analysis. We recruited community pharmacists, with experience dispensing psychotropics, at a minimum, through multiple mechanisms (e.g., professional associations) in a convenience sampling approach. Potential participants were offered the option of focus groups or interviews. Results Data were collected from one focus group and two interviews involving six pharmacists. Theoretical Domains Framework coding was primarily weighted in two domains: social/professional role and identity and environmental context and resources. We identified five main themes in the experiences of pharmacists in mental illness and addictions care: competing interests, demands, and time; relationships, rapport, and trust; stigma; collaboration and triage; and role expectations and clarity. Conclusions Pharmacists are not practicing to their full scope of practice in mental illness and addictions care for several reasons including limitations within the work environment and lack of structures and processes in place to be fully engaged as health care professionals. More research and policy work are needed to examine better integration of pharmacists as members of the mental health care team in communities.